REPRESENTASI KEKUASAAN DAN RESISTENSI DALAM NOVEL TERUSLAH BODOH JANGAN PINTAR KARYA TERE LIYE - Dita; Amirudin Rahim; Saidiman (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the representation of power and resistance in the novel. The type of research used is library research. The research method is descriptive qualitative. Data collection techniques were carried out through reading and note-taking. Data were analyzed using a sociology of literature approach, which was carried out in four stages: data identification, data classification, data description, and interpretation. The data in this study consisted of words, sentences, and events contained in the novel, using Faucault's theory of power. In his view, power is not centered on a single point but spreads across social networks or relations. The results of the study indicate the existence of power in the novel, represented through power relations over thoughts, in the form of domination, stigmatization, manipulation of thought, control of thought, and power relations over the social body. Furthermore, resistance emerges as a form of rejection by those who feel oppressed, either openly or covertly. Keywords: representation of power, resistance, novel